Kinetoplastids biology, from the group phylogeny and evolution into the secrets of the mitochondrion of one representative: Trypanosoma brucei, the model organism in which new roles of the evolutionary conserved genes can be explored - Týč, Jiří (Jihočeská univerzita, 2015)
This thesis is composed of two topics, for which trypanosomatids and evolution are common denominators. First part deals with phylogenetic relationships among monoxenous trypanosomatids, with emphasis on flagellates parasitizing dipteran hosts, analyzed mainly from biogeographical and evolutionary perspectives. Second part focuses on the trypanosomatid Trypanosoma brucei, causative agent of severe diseases, which serves as a model organism for functional studies of evolutionary conserved mitochondrial proteins, in particular those involved in replication, maintenance and expression of the mitochondrial genome, also termed the kinetoplast. This thesis identified the mtHsp70/mtHsp40 chaperone machinery as an essential component of replication and maintenance of the kinetoplast, and also identified numerous conditions under which mtHsp70 has a tendency to aggregate. Moreover, several conserved proteins, previously identified to be part of the mitochondrial ribosome, were shown to be important for translation of the mitochondrial transcripts.
Kinetoplastids biology, from the group phylogeny and evolution into the secrets of the mitochondrion of one representative: Trypanosoma brucei, the model organism in which new roles of the evolutionary conserved genes can be explored
Keywords: molecular biology; evolution; Trypanosomatids; Trypanosoma brucei; mitochondrion; ribosome; mtHsp70; mtHsp40; kinetoplast; mitochondrial translation; molecular biology; evolution; Trypanosomatids; Trypanosoma brucei; mitochondrion; ribosome; mtHsp70; mtHsp40; kinetoplast; mitochondrial translation